Permanent observatories as tools for ex-post assessment: The French case study - Alain Bonnafous (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2014)
In France, the obligation to conduct an ex-post assessment is relatively recent (1982) but it has in fact revealed some methodological problems that flow from the retrospective nature of the exercise. This report shows that some of those difficulties can be overcome through the establishment of permanent observatories. It presents examples of such observatories, with a particular focus on motorway ("autoroute", or "freeway" in North American usage) investments. A particular case is then investigated, concerning the socioeconomic observatory on the effects of the Sud-Europe-Atlantique [South-Europe-Atlantic] high-speed train line that is now under construction. This major project ( exteuro7.8 billion) has been let under a concession. The concession contract calls for the establishment of an observatory that also covers the construction period and is to remain in operation for 10 years after the line comes into service, or until 2027. Besides an overall presentation of the mechanism, the report deals in particular with the metrological precautions that must be taken in order to monitor the multimodal offer of transport for the areas concerned. One of the key issues here, in fact, is to explain the discrepancies between forecast and projected and actual traffic, an explanation that may be more complete than in the ex-post evaluation procedure.
Keywords: 330; Verkehrsinfrastruktur; Verkehrspolitik; Wirkungsanalyse; Frankreich